2017
DOI: 10.1590/2317-1782/20172016187
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas do trato vocal e índice de desvantagem vocal para o canto moderno em cantores evangélicos

Abstract: RESUMO Objetivo correlacionar os sintomas de desconforto do trato vocal e desvantagem de voz percebida em homens e mulheres cantores evangélicos. Método participaram 100 cantores evangélicos, 50 do gênero masculino e 50 do feminino. Todos os participantes responderam a dois questionários: Escala de Desconforto do trato vocal (EDTV) e o Índice de Desvantagem para o Canto Moderno (IDCM). Foi realizada a comparação entre os gêneros, tanto em relação aos sintomas do trato vocal como em relação aos índices de IDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…There was a majority of female subjects (54 ± 2%), which is in agreement with results from some studies, 4 10 12 13 15 16 17 18 19 and in contrast with results from other studies. 2 5 20 This suggests that men present a greater voice handicap when compared with women.…”
Section: Discussionsupporting
confidence: 91%
“…There was a majority of female subjects (54 ± 2%), which is in agreement with results from some studies, 4 10 12 13 15 16 17 18 19 and in contrast with results from other studies. 2 5 20 This suggests that men present a greater voice handicap when compared with women.…”
Section: Discussionsupporting
confidence: 91%
“…We found statistically significant correlations between both subscales of VTD and SVHI. This result is in line with the study by Pinheiro et al who examined 100 church gospel singers and found significant correlations between the VTD scale and Modern Singing Handicap Index (MSHI) ( 74 ) ( Table 12 ).…”
Section: Discussionsupporting
confidence: 92%
“…1st Phase: The survey was developed after identifying studies with similar goals regarding voice disorders [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The findings were based on the search strategy of the authors' previous research [36].…”
Section: Questionnaire Developmentmentioning
confidence: 99%